1999
DOI: 10.1016/s0006-3495(99)77160-2
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Field Heterogeneity at the Heme of c-Type Cytochromes by Spectral Hole Burning Spectroscopy and Electrostatic Calculations

Abstract: We report on a comparative investigation of the heme pocket fields of two Zn-substituted c-type cytochromes-namely yeast and horse heart cytochromes c-using a combination of hole burning Stark spectroscopy and electrostatic calculations. The spectral hole burning experiments are consistent with different pocket fields experienced at the hemes of the respective cytochromes. In the case of horse heart Zn-cytochrome c, two distinguishable electronic origins with different electrostatic properties are observed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 53 publications
(56 reference statements)
8
43
0
Order By: Relevance
“…The Stark-spectra show rather convincingly that it is the red conformation which does not seem to be populated in cytochrome c from yeast. These findings are strongly supported by MD-simulations and electrostatic calculations which demonstrate that the conformational phase space sampled by the cytochrome c from horse heart is significantly larger than the respective one sampled by cytochrome c from yeast [70].…”
Section: Stark-effect Spectroscopy and Electric Fields In Protein Cavmentioning
confidence: 54%
“…The Stark-spectra show rather convincingly that it is the red conformation which does not seem to be populated in cytochrome c from yeast. These findings are strongly supported by MD-simulations and electrostatic calculations which demonstrate that the conformational phase space sampled by the cytochrome c from horse heart is significantly larger than the respective one sampled by cytochrome c from yeast [70].…”
Section: Stark-effect Spectroscopy and Electric Fields In Protein Cavmentioning
confidence: 54%
“…They showed that, for the same quadrupole coupling, yc exhibits a substantially lower splitting than hhc, owing to the fact that the difference ‫ץ‬E x / ‫ץ‬x − ‫ץ‬E y / ‫ץ‬E y is much smaller in the former, as shown earlier by Laberge et al 5 ent of the electric field at the heme. This is in line with our earlier prediction that a nonuniform rather than a uniform field causes the splitting.…”
Section: Resultsmentioning
confidence: 70%
“…Additionally, the internal electric field created by ionizable and polar side chains causes a perturbation of the heme's potential energy. [2][3][4][5][6][7] Numerous studies have been performed to explore the influence of the proximal and distal ligands on the oxidation and spin state of the central iron atom. The proximal ligand ͑histidine in most cases͒ was found to exert a particularly strong influence on the heme iron as well as on the symmetry of the heme macrocycle.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence hole burning experiments on heme proteins with Zn-substituted heme groups revealed electric field strengths in the range of 10 7 /cm. Theoretical calculations based on the solution of Laplace equations yielded values in the same order of magnitude [36]. Manas et al argued on theoretical grounds that this internal electric field can cause a splitting of both the -and -band, if the field vector does not exactly bisect the two transition dipole moments of the twofold degenerate electronic transitions [35].…”
Section: Probing the Electric Field Of The Protein In The Heme Planementioning
confidence: 98%
“…In spite of a rather asymmetric heme environment and strong heme-protein interactions via the two axial ligands [10,30,31], the thioether bridges [32], the internal electric field at the heme [33][34][35][36][37][38], and to a lesser extent substituent-hydrogen bonding [25,26,[39][40][41] and multiple van der Waals contacts [42], spectroscopists have for a long period of time considered the heme as exhibiting an ideal D 4h -symmetry. This was (and in part still is) particularly true for the interpretation of optical absorption and resonance Raman data [43][44][45][46][47][48][49].…”
Section: Asymmetric Deformations Of the Functional Heme Groupmentioning
confidence: 99%